UPAYA PENATAAN PASAR PAJAK LAMA OLEH PEMERINTAH DAERAH KABUPATEN ROKAN HILIR TAHUN 2017 - Bastian, Ega Van; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Old Tax Market is a market that still causes a lot of problems, the problem that arises is that there are still many Street Vendors (PKL) who sell on the road due to the inadequate number of kiosks and kiosks with the number of traders so many traders cannot sell materials the merchandise is in kiosks and stalls that make them have to sell on the road and of course cause traffic flow to become jammed even causing fatalities due to traffic accidents in the Old Tax market area. The existing parking conditions are also inadequate which makes many traders park their vehicles for loading and unloading activities and the buyers also park in the streets due to the limited parking provided so that road users cross and make traffic jams, even though the old tax market stands in the causeway which is the gateway to Riau Province from the direction of North Sumatra. Other conditions that exist are the limited facilities and infrastructure such as public toilets, so that if the traders and buyers will go to the toilet they must queue first.The formulation of the problem in this study is (1) What are the efforts in structuring the old tax market by the Regional Government of Rokan Hilir Regency in 2017 ?, (2) what are the obstacles faced in the effort to restructure the old tax market by the Regional Government of Rokan Hilir Regency in 2017?In this study researchers tried to explain the efforts in structuring the old tax market by the Regional Government of Rokan Hilir Regency. Data collection techniques in this study were using interview techniques and documentation. Based on interviews with all informants and based on supporting data and information obtained by researchers when conducting research. It can be concluded that efforts to restructure the old tax market by the Regional Government of Rokan Hilir Regency have not been going well. Because of the first several factors: lack of awareness of the old tax market traders in Bagan Sinembah Sub-District, Rokan Hilir District, Second: Lack of facilities and infrastructure such as operational funds and operational cars.Keywords: Efforts, Arrangement, Old Taxes